A Korean agricultural general equilibrium model of trade - Yoon, Haejin (1989)
This study represents an attempt to analyze the effect of Korea's agricultural trade liberalization on resource allocation and welfare. For this purpose, this study has constructed a computable general equilibrium model which is tailored to study the agricultural aspect of the Korean economy. The Korean Agricultural General Equilbrium Model (KAGEM) allows one to simulate and examine various economic policies such as internal and external tax policies. The KAGEM has two different versions: Walrasian and non-Walrasian. Generally, results show that tariff reduction discourages agricultural production activity more than other sector's. However, agricultural protection through the subsidy program seems to have a positive effect on output and national welfare. It is observed that trade liberalization may reduce welfare level in the short run. As expected, wage fixity brings more loss of consumer surplus and of output and employment under trade liberalization. Throughout the study, a strong general equilibrium defect seems to prevail when external policy changes are introduced. Thus the KAGEM is shown to be fully equipped to provide the general equilibrium effect of agricultural trade liberalization on activities of various economic agents.
Includes bibliographical references (pages 256-257).
Keywords: Computable general equilibrium models; Free trade |x Korea (South).; Equilibrium (Economics).